High Leptospira Diversity in Animals and Humans Complicates the Search for Common Reservoirs of Human Disease in Rural Ecuador. - Veronica Barragan; Jorge Chiriboga; Erin Miller; Sonora Olivas; Dawn Birdsell; Crystal Hepp; Heidie Hornstra; James M Schupp; Melba Morales; Manuel Gonzalez; Soraya Reyes; Carmen de la Cruz; et al. (PLoS Neglected Tropical Diseases, 2016)
BACKGROUND:Leptospirosis is a zoonotic disease responsible for high morbidity around the world, especially in tropical and low income countries. Rats are thought to be the main vector of human leptospirosis in urban settings. However, differences between urban and low-income rural communities provide additional insights into the epidemiology of the disease. METHODOLOGY/PRINCIPAL FINDINGS:Our study was conducted in two low-income rural communities near the coast of Ecuador. We detected and characterized infectious leptospira DNA in a wide variety of samples using new real time quantitative PCR assays and amplicon sequencing. We detected infectious leptospira in a high percentage of febrile patients (14.7%). In contrast to previous studies on leptospirosis risk factors, higher positivity was not found in rats (3.0%) but rather in cows (35.8%) and pigs (21.1%). Six leptospira species were identified (L. borgpetersenii, L kirschnerii, L santarosai, L. interrogans, L noguchii, and an intermediate species within the L. licerasiae and L. wolffii clade) and no significant differences in the species of leptospira present in each animal species was detected (χ2 = 9.89, adj.p-value = 0.27). CONCLUSIONS/SIGNIFICANCE:A large portion of the world's human population lives in low-income, rural communities, however, there is limited information about leptospirosis transmission dynamics in these settings. In these areas, exposure to peridomestic livestock is particularly common and high prevalence of infectious leptospira in cows and pigs suggest that they may be the most important reservoir for human transmission. Genotyping clinical samples show that multiple species of leptospira are involved in human disease. As these genotypes were also detected in samples from a variety of animals, genotype data must be used in conjunction with epidemiological data to provide evidence of transmission and the importance of different potential leptospirosis reservoirs.